**Directions (1 – 10): In these questions, a relationship between different elements is shown in each statement. The statements are followed by two conclusions. Give answer-**

a) if only
conclusion I is true.

b) if only
conclusion II is true.

c) if either
conclusion I or II is true.

d) if neither
conclusion I nor II is true.

e) if both
conclusion I and II are true.

**1.**

**Statements :**E > B ≥ A < M, N > A > P

**Conclusions :**

**I.**N > B

**II.**M > N

**2.**

**Statements :**N = E ≤ P > Q, P ≥ S

**Conclusions :**

**I.**N ≥ S

**II.**S > Q

**3.**

**Statements :**

**V < P > Q = T ≥ R, Q ≤ S**

**Conclusions :**

**I.**T ≥ S

**II.**S ≥ V

**4. Statements :**L = I ≥ J < K, J ≥ M

**Conclusions :**

**I.**K > M

**II.**L ≥ M

**5. Statements :**A > B ≥ C < L, D < C ≤ E

**Conclusions :**

**I.**E > L

**II.**E ≥ B

**6. Statements :**

**S ≤ A > P, B ≥ A < C**

**Conclusions :**

**I.**B ≥ S

**II.**C > P

**7. Statements :**

**M > P ≤ N < U, N > B, A ≥ U**

**Conclusions :**

**I.**M > B

**II.**A > B

**8. Statements :**W ≥ X = V ≤ Y, U < X ≥ Z

**Conclusions :**

**I.**W ≥ U

**II.**Y ≥ U

**(9 – 10): Statements :**H ≤ G < V ≥ U, G ≤ S, P > V

**9.**

**Conclusions :**

**I.**H < P

**II.**U ≤ S

**10.**

**Conclusions :**

**I.**S ≥ H

**II.**U < P

**Answers:**

**1. D)**Given:

E > B ≥ A
< M ...(i)

N > A >
P ...(ii)

Combining
both, we get,

E > B ≥ A > P and

E > B ≥ A < N and

M > A <
N

We can’t
compare N and B. So, conclusion I is not true. Again, we can’t compare M and N.
So, conclusion II is also not true.

**2. D)**Given :

N = E ≤ P
> Q ...(i)

P ≥ S ...(ii)

Combining (i)
and (ii) we get,

N = E ≤ P ≥ S
and

Q < P ≥ S

We can’t
compare N and S. So, conclusion I is not true. Again, we can’t compare S and Q.
So, conclusion II is not true.

**3. D)**Given :

V < P >
Q = T ≥ R ...(i)

Q ≤ S ...(ii)

Combining (i)
and (ii) we get,

V < P >
Q = T ≤ S and

S ≥ Q = T ≥ R

Hence, S ≥ T. So, conclusion I is not true.

Again, we
can’t compare S and V. So, conclusion II also is not true.

**4. E)**Given :

L = I ≥ J < K ...(i)

J ≥ M ...(ii)

Combining (i)
and (ii) we get,

L = I ≥ J ≥ M and

K > J ≥ M

Conclusion I
is true.

Again,
conclusion II is also true.

**5. D)**Given :

A > B ≥ C
< L ...(i)

D < C ≤ E
...(ii)

Combining (i)
and (ii) we get,

A > B ≥ C
> D and

A > B ≥ C ≤
E and

D < C <
L and

E ≥ C < L

We can’t
compare E and L. So, conclusion I is not true.

Again, we
can’t compare E and B. So, conclusion II is also not true.

**6. E)**S ≤ A > P ............. (i)

B ≥ A < C
........ (ii)

Combining
(i), and (ii), we get

S ≤ A ≤ B and

S ≤ A < C
and

B ≥ A > P
and

C > A >
P

(I) B ≥ S is
true. So, conclusion I is true.

(II) C > P
is true. So, conclusion II is true.

**7. B)**Given:

M > P ≤ N
< U .............. (i)

N > B
.......................... (ii)

A ≥ U
.................................... (iii)

Combining
(i), (ii) and (iii), we get

M > P ≤ N
> B and

M > P ≤ N
< U ≤ A and

B < N <
U ≤ A

(I) We can’t
compare M and B. So, conclusion I is not true.

(II) A > B
is true. So, conclusion II is true.

**8. D)**Given:

W ≥ X = V ≤ Y
............... (i)

U < X ≥ Z
................. (ii)

Combining (i)
and (ii), we get

W ≥ X > U
and

U < X = V ≤
Y and

W ≥ X ≤ Z and

Z ≤ X = V ≤ Y

(I) W > U,
is true. So, W U is not ture. Thus, conclusion I is
not true.

(II) Y > U
is true. So, Y U is not true. Thus, conclusion II is
not true.

**(9 – 10):**

Given:

H ≤ G < V ≥
U .................. (i)

G ≤ S
............................... (ii)

P > V
............................ (iii)

Combining
(i), (ii) and (iii), we get

H ≤ G ≤ S and

S ≥ G < V ≥
U and

P > V ≥ U
and

H ≤ G < V
< P and

P > V >
G S

**9. A)**

(I) P > H
is true. So, conclusion I is true.

(II) We can’t
compare S and U. So, conclusion II is nottrue.

**10. E)**

(I) S ≥ H is
true. So, conclusion I is true.

(II) U < P
is true. So, conclusion II is also true.